Rural Ageds’ Awareness and Perception of Climate Variability in Kanke and Riyom Local Government Areas of Plateau State, Nigeria - Kehinde Olayinka Popoola; Sunday Adesola Ajayi (Archives of Current Research International, 2019)
This study examined rural aged’s awareness and perception of climate variability in Riyom and Kanke LGAs of Plateau State. There was random selection of one local government area in the upper plateau (Kanke LGA) and another local government area in the lower plain of the plateau (Riyom LGA) because of the constrasting climate which is dominantly influenced by the relief in the area. The research made use of quantitative data which were obtained through structured questionnaire administered to aged male, and aged female available in the selected houses (the aged are people 60 years and over in age) in the selected rural communities of Riyom and Kanke LGAs of Plateau State, Nigeria. Where there was no combination of the two (aged men and aged women), either of the two was also sufficient. The analysis was done using SPSS. The study revealed there were more aged males than aged females. 72.7% were in the age range 60-69; more than 80% were crop farmers and about 62.6% earned less than N20,000 (56 USD) per month. Also 86.3% have heard of climate change; 80.6% felt they understood climate change; while 95% felt the climatic variability was increasingly changing. The study also revealed that age and LGAs were major determinant of perception and awareness of climate change. This study therefore concluded that in order to have an effective intervention for climate change impact on the rural aged, their perception and response to climate change and also peculiarities of the areas must be taken into consideration.